Factors and Relationships Influencing Self-Regulated Learning Among ICT Students In Australian Universities - Balapumi, Rohini; Aitken, Ashley (IADIS Press, 2012)
Self-regulated learning has shown to positively impact academic achievement in educational settings. This research aims to understand the level of self-regulated learning among students, specifically in the area of ICT in Australian universities, and also to investigate the reciprocal relation between university lecturers and students in cultivating Self- Regulated Learning (SRL) in the students. Interviews with several lecturers and students will be conducted during the preliminary phase of the research to identify the factors that influence students SRL in university environment. Based on review of past literature studies and the outcome from the preliminary phase, a preliminary theoretical framework will be developed. This research will employ a quantitative approach utilising survey method, will collect empirical data needed to test the theoretical model developed for the research. Statistical tests will be conducted to determine the relationship of the factors and related indicators on the students SRL, as developed in the preliminary theoretical framework. The outcome of this study will assist Australian universities to focus on and move towards a better understanding of selfregulated learning concept and to better able to promote and facilitate SRL among students. It also will help to invest time and effort on the factors that influence the internalisation of self-regulatory skills among students at university education, in order to contribute to the development of educational aims in the teaching and learning field. The research will be undertaken within a three-year period, has minimal resource requirements and shall obtain ethics approval and handle data as required.